KING-KU: Driving Customer Loyalty through Customer Satisfaction on KingGarage Kudus - Ulfa, Adilla Kustya; Haziroh, Awanis Linati; Rahayuningtyas, Tri Esti; Fatmawati, Elia Resha; Kanaya, Fadia Zulfa; Yulianto, Ahmad Rudi (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
Competition in the automotive service industry has intensified, marked by the growing number of highly rated repair shops in Kudus Regency. As a newly established workshop in 2022, KingGarage Kudus faces challenges in building customer loyalty, as preliminary findings indicate low levels of repeat purchases and customer referrals. This study aims to examine the effects of service quality and brand image on customer loyalty, with customer satisfaction serving as a mediating variable that strengthens relational outcomes. A quantitative research approach was employed, with data collected through a closed-ended questionnaire using a Likert scale to capture customer perceptions accurately. The sample consisted of KingGarage Kudus customers selected through purposive sampling based on predefined criteria related to service experience. Data were analyzed using SmartPLS 4, including outer model evaluation, inner model assessment, coefficient of determination (R²), and hypothesis testing to ensure robust statistical validation. The findings reveal that service quality and brand image have a positive and significant effect on customer loyalty. Furthermore, customer satisfaction significantly mediates the relationship between service quality, brand image, and customer loyalty, indicating its central role in loyalty formation. These results highlight the strategic importance of enhancing service quality and strengthening brand image to foster customer satisfaction and reinforce customer loyalty, thereby enabling automotive service providers to sustain their competitive advantage in a highly dynamic and competitive industry environment.